Degradation of dynamic mechanical properties of glass fiber reinforced polyester composite pipes after immersion in various temperatures. (October 2014) - Mouallif, Ilias; Latrach, Abdelkhalek; Chergui, M'hamed; Benali, Abdelkader; Elghorba, Mohammed; Mouallif, Zakaria; Hangouët, Jean-Pierre; Barbe, Nicolas
This paper reports the effect of sulfuric acid solution absorption on the dynamic mechanical properties of glass fiber reinforced polyester composites. An experimental device is presented that allows the effect of changes of environment and temperature on both the diffusion coefficient and the maximum moisture content to be measured. The results indicate that increased temperature raises both the diffusion coefficient and the maximum absorbed moisture of all the composite materials used in this study. Moreover, it has been noted that specimens exposed to higher temperature absorb much more water than those held at low temperature. The dynamic mechanical properties of glass fiber reinforced polyester were found to be highly affected by the presence of absorbed solvents in the specimen and increases in temperature. A fractographic study has been conducted using a scanning electron microscope of the surfaces of specimens broken by tensile testing. Observations indicate that increased immersion time increases the deterioration of the fibre/matrix interface.